Syria's uprising and the fracturing of the Levant / Emile Hokayem - Hokayem, Emile (Adelphi (Series) (International Institute for Strategic Studies), 2013)
As an upbeat and peaceful uprising quickly and brutally descended into a zero-sum civil war, Syria has crumbled from a regional player into an arena in which a multitude of local and foreign actors compete. The volatile regional fault lines that run through Syria have ruptured during this conflict, and the course of events in this fragile yet strategically significant country will profoundly shape the future of the Levant.